Effect of High-Altitude Exposure on the Heart - Lan Huang (Cardiology Discovery)
High altitude brings a great physiological change in human beings, both during short-term exposure and in lifelong residents, especially in the cardiovascular system. Hypoxia notably induces pulmonary vasoconstriction, thus resulting in a moderate increase in pulmonary arterial pressure. Acclimatized inhabitants exhibit lower pulmonary pressure and better exercise capacity than lowlanders during short-term high-altitude exposure. Rapid ascent to high altitude without adequate acclimatization can cause high-altitude pulmonary edema in susceptible individuals, with a rapid increase in pulmonary pressure. Cardiac output increases initially following acute high-altitude exposure and returns to normal as at sea level after a few days of acclimatization. Ventricular volumes at high altitude change consistently with decreases in plasma volume. Left ventricular systolic function is enhanced after acute high-altitude exposure and during chronic acclimatization. However, there are controversies on whether right ventricular systolic function is preserved or decreases after high-altitude exposure, probably due to variable hypoxic pulmonary vasoconstriction. High altitude induces altered ventricular diastolic patterns. Recently, a new perspective has emerged, whereby ventricular intrinsic relaxation is not impaired, as assessed by untwisting through speckle-tracking imaging. Persistent hypoxic pulmonary hypertension probably induced right ventricular dilation and hypertrophy, and even right heart failure, described as high-altitude heart diseases. Descent to lower altitude should be the best treatment for them, and potential pharmacological agents majorly focus on the inhabitation of pulmonary vasoconstriction, such as phosphodiesterase-5 inhibitors and endothelin receptor antagonists. Evidence on the risks of high-altitude exposure for patients with previous cardiovascular diseases is limited, and thus they should be prudent when ascending to high altitude. Further randomized large-scale studies are needed to explore cardiac performance at high altitudes and provide more evidence for the prevention and clinical management of medical complications at high altitude.